Trends in Area, Production and Productivity of Castor in Telangana - , Nivetha S; , Shakuntala Devi I; , Lavanya T; , Aruna K (Archives of Current Research International, 2024)
Aims: To analyse the trends in area, production and productivity of castor in Telangana and major erstwhile districts of Telangana. The main purpose of the study is to understand the growth rate of castor in a region of Telangana, as India is the largest exporter of castor oil, which has multiple industrial applications. Methodology: The secondary data of the area, production and productivity of castor from 2001-02 to 2022-23 were collected from the Directorate of Economics and Statistics. The Compound Annual Growth Rate (CAGR) was used to analyse the time-series data of castor. CAGR was calculated for 3 periods -Period I (2001-02 to 2011-12), Period II (2012-13 to 2022-23), Overall Period (2001-23). Results: The results showed a decreasing trend in both castor area and production. But castor productivity observed a positive growth rate in Telangana and the major erstwhile castor-growing districts like Mahbubnagar and Medak. However, few districts like Rangareddy, Nalgonda, and Warangal showed negative trends in productivity during Period I. The study highlighted a decline in the castor area due to the incidence of diseases like Botrytis, shifting to other crops such as cotton and climate variability. Conclusion: The study indicated that the decline in the castor area is a major concern and this study will be useful in agricultural policy making to take appropriate actions to reverse the declining trends of castor cultivation in Telangana.